Health impacts due to deficient water access - Razzolini, Maria Tereza Pepe; Günther, Wanda Maria Risso (Saúde e Sociedade, 2008)
Regular water access has caused concern, mainly in developing countries and especially in periurban areas, where socially excluded people live. The aim of this work is to approach water access issues in periurban regions. A bibliographical survey was carried out in the Pubmed, Medline and SciELO databases, as well as in reports from WHO, PAHO, IBGE and Brazilian Ministries. A non-existent or precarious water access represents a risk situation that increases the incidence of infectious diseases and the prevalence of chronic diseases that affect susceptible groups. The criteria to establish water access level consider distance and time to reach water sources, collected volume, water demand and the priority level of intervention actions. Factors such as handling - the way in which collection, transport, storage and use are carried out -, pathogens determination in water sources and the population's routine practices can interfere in the sanitary quality of water. Pathogens determination in water sources is important to highlight health risks, and the etiologic agent identification can indicate contamination origin. Daily activity can contribute to disseminate pathogenic microorganisms among people and to spread infectious diseases. The way to change this scenario is to implement integrated public policies in the sectors of urban development, housing, sanitation and health. The main goal is to promote and protect people's health and to face the complexity of factors that disclose their vulnerability.